Crystal structure resolution of an insulator due to the cooperative Jahn–Teller effect through Bader's theory: the challenging case of cobaltite oxide Y114. Issue 15 (3rd April 2018) - Tantardini, Christian; Benassi, Enrico
Abstract : Cobaltite YBaCo4 O7, abbreviated as Y114, is one of the most thoroughly investigated perovskites, owing largely to its interesting magnetic properties. Abstract : Cobaltite YBaCo4 O7, abbreviated as Y114, is one of the most thoroughly investigated perovskites, owing largely to its interesting magnetic properties. Y114 is an insulator as a result of the cooperative Jahn–Teller effect, where one electron jumps quickly from one cobalt site to another, making it impossible to experimentally assign the correct oxidation state for each of the two cobalt sites. The present study solved the ambiguity by means of state-of-the-art DFT calculations. The two cobalt sites were differentiated through an analysis of charge density within the framework of the quantum theory of atoms in molecules.